Reconstructing security after conflict : security sector reform in Sierra Leone - Jackson, Paul, 1968 April 24-; Albrecht, Peter, 1976- (Basingstoke, Hampshire [U.K.] ; New York : Palgrave Macmillan, 2011)
This volume provides a long-term evaluation and analysis of the UK's involvement in Sierra Leone before and after the conflict which ended in 2002. This book looks at how UK intervention moved from initial involvement through to war fighting and then post-conflict reconstruction, specifically of the security infrastructure. --Publisher's description.
Introduction -- How did SSR in Sierra Leone impact on international policy-making on SSR? -- Security and Sierra Leone up until the end of the conflict -- The development of an SSR concept, 2002-2005 -- Consolidation and development, 2005-2007 -- Cross-cutting themes throughout the period in Sierra Leone and beyond -- Conclusions.
Includes bibliographical references (pages 222-226) and index.
Keywords: National security -- Sierra Leone; Peace-building -- Sierra Leone; Military assistance, British -- Sierra Leone